Pengetahuan Konservasi Tradisional Burung Endemik pada Masyarakat Kampung Soaib di Distrik Kemtuk, Kabupaten Jayapura - Matias Beno; Henderite L. Ohee (Jurnal Biologi Papua, 2009)
This study was to investigate the endemic birds, local knowledge and the conservation efforts on the bird species. The study was conducted in the period from February 2007 to May 2008. Methods used including observation, interviews, documentation, description and literature review. The results showed that there were 11 spesies of endemic birds occured in Soaib village: Cassowary (Casuarius unappendiculatus), Yellow-crested Cockatoo (Cacatua galerita), two species of Megapodes; (Aypepodius arfakianus) and (Megapodius freycinet), Papuan Hornbill (Rhyticeros plicatus), Victoria Crowned-pigeon (Goura victoria), Palm Cockatoo (Prombosciger atterimus), Parrot (Psittrichas fulgidus), Papuan crow (Cracticus cassicus) Bird of Paradise (Paradiseae sp). Local people determined the forest in three different types; primary forest, buffer zone between primary and secondary forest and secondary forest. Primary forest was being the habitat for 11 endemic birds. These birds were hunted by local people for meat consumption and cultural purposes excepted the Papuan hornbill (Rhyticeros plicatus) and Papuan crow (Cracticus cassicus). Bird of Paradise (Paradiseae sp), and yellow-crested Cockatoo (Cacatua galerita) were captured to be sold in the market. This was happened because of lack information and education about the role of the birds in forest ecosystem. Key words: Traditional conservation, endemic birds, Soaib village, Jayapura